Structural investigation of human cystine/glutamate antiporter system xc− (Sxc−) using homology modeling and molecular dynamics - Hang, Tran Dieu; Hung, Huynh Minh; Beckers, Pauline; Desmet, Nathalie; Lamrani, Mohamed; Massie, Ann; Hermans, Emmanuel; Vanommeslaeghe, Kenno (Frontiers in Molecular Biosciences, 2022)
The cystine/glutamate antiporter system xc- (Sxc-) belongs to the SLC7 family of plasma membrane transporters. It exports intracellular glutamate along the latter’s concentration gradient as a driving force for cellular uptake of cystine. Once imported, cystine is mainly used for the production of glutathione, a tripeptide thiol crucial in maintenance of redox homeostasis and protection of cells against oxidative stress. Overexpression of Sxc- has been found in several cancer cells, where it is thought to counteract the increased oxidative stress. In addition, Sxc- is important in the central nervous system, playing a complex role in regulating glutamatergic neurotransmission and glutamate toxicity. Accordingly, this transporter is considered a potential target for the treatment of cancer as well as neurodegenerative diseases. Till now, no specific inhibitors are available. We herein present four conformations of Sxc- along its transport pathway, obtained using multi-template homology modeling and refined by means of Molecular Dynamics. Comparison with a very recently released cryo-EM structure revealed an excellent agreement with our inward-open conformation. Intriguingly, our models contain a structured N-terminal domain that is unresolved in the experimental structures and is thought to play a gating role in the transport mechanism of other SLC7 family members. In contrast to the inward-open model, there is no direct experimental counterpart for the other three conformations we obtained, although they are in fair agreement with the other stages of the transport mechanism seen in other SLC7 transporters. Therefore, our models open the prospect for targeting alternative Sxc- conformations in structure-based drug design efforts.